Preface 2019, 32(1) - Chairuangsri, Torranin (Microscopy and Microanalysis Research – The Journal of The Microscopy Society of Thailand, 2019)
Microscopy and Microanalysis Research-The Journal of The Microscopy Society of Thailand (Microsc. Microanal. Res.) is formerly known as Newsletter Electron Microscopy Society of Thailand (1984-1987), the Journal of the Electron Microscopy Society of Thailand (JEMST Vol. 1-21, 1987-2016) and the Journal of Microscopy Society of Thailand (JMST Vol. 22-29, 2008-2016). The journal title has been changed to Microsc. Microanal. Res. since January 2017 (Vol. 30, No.1, January-July 2017) to get more attention from international readers and authors. Microsc. Microanal. Res. publishes original research articles two volumes a year. Articles include the applications of microscopy and microanalysis to important problems in the fields of physical science and biological science. The originality and significance of the research and the quality of the microscopy or microanalysis involved are the criteria for acceptance of manuscripts. This issue contains 10 papers in the field of Biological Science. These works were selected from those presented in the 36th International Conference of the Microscopy Society of Thailand (MST36) which was held at Rama Garden Hotel, Bangkok, Thailand, on 26-29 March 2019. The conference was co-organized by the Faculty of Science, Kasetsart University and the Microscopy Society of Thailand.